Design of the gamifying anti-bullying education: a transformative approach with the giant snakes and ladders bullying game - Nurdianawati, Nita Dewi; Slamet , ST. Y.; Indriayu , Mintasih (Universitas Ahmad Dahlan, 2025)
Bullying in elementary school environments is a serious problem that can hinder children's emotional and social development. This study aims to provide anti-bullying education to elementary school students through interactive game media, namely Giant Bullying Snakes and Ladders. The method used was an in-depth interview with elementary school teachers in Pracimantoro District, Wonogiri Regency. This interview aims to obtain information about the forms of bullying behavior that often occur in schools and educational efforts that have been implemented previously. Based on the results of data analysis, researchers designed a creative solution in the form of an educational game that is not only fun but also full of anti-bullying moral messages. This game is designed on a large scale to attract students' attention and can be played in groups. Each box in the game contains illustrations and educational messages, such as an invitation to stop bullying and empathy for friends. The results of implementing this game show that students become more active in discussing bullying and are more courageous in saying